Peran Manajemen Kurikulum dalam Mengembangkan Kompetensi Peserta Didik di Lembaga Pelatihan Kerja Irma - Ayi Najmul Hidayat; Rismawan Rismawan; Parid Abdul Hadi (Journal on Education, 2023)
Curriculum management is a cooperative, comprehensive, systemic and systematic curriculum management system. LPK (Job Training Institute) is a non-formal educational institution organized for the community to provide knowledge and skills that must have a curriculum in accordance with government regulations. In this study, a qualitative approach was used with an analytical descriptive method. Conclusions The results of this research are that the job training institute (IRMA) uses a curriculum that is guided by the Indonesian National Work Competency Standards (SKKNI) so that graduates from Irma training institutions have the competencies needed by the world of work by delivering material to training participants using the Active, Creative, Effective, and Fun Learning Model (PAKEM) in implementing the curriculum based on the Syllabus and lesson plans that have been provided.